Analisis Faktor-Faktor Teknologi dan Sosial Budaya yang Mengancam Keberlanjutan Kemandirian Pangan Pokok di Provinsi Jawa Barat, Indonesia - Fitrah Gunadi; Rizal Sjarief Sjaiful Nazli; Eka Intan Kumala Putri; Bambang Pramudya Noorachmat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Sustainability of food self-sufficiency in the West Java Province experiences strong pressure along with increasing economic development, the process of urbanization, population growth and the effects of climate change. The objective of this study is to identify technological and socio-cultural factors that can threatening the sustainability of food self-sufficiency in West Java Province. This study uses multidimensional scaling analysis to assess the sustainability index and status and supported by a descriptive analysis of key factors that can provide inhibiting factors for the sustainability of food self-sufficiency. The results of the analysis describe that the ecological, economic and institutional aspects have sufficient influence on sustainability in food self-sufficiency, while the socio-cultural aspects and aspects of technology provide less sustainable effects in supporting the sustainability of food self-sufficiency. Factors in the use of certified seeds, area of paddy fields and irrigated rice fields, use of tools and machines for rice production and rice cropping indexes are key factors in technological aspects that can be a threat to the sustainability of food self-sufficiency. While the threat to the sustainability of food self-sufficiency in the socio-cultural aspects come from the factor of the number of workers in the food crops sub-sector, the pattern of consumption of carbohydrate food in the community and the distribution of rice. Governance of these key factors is key in developing sustainability of food self-sufficiency in West Java Province.